SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS as well as preparation method and application of SPBI-based composite proton exchange membrane

By incorporating sulfonated octphenyl SPOSS into the DMFC proton exchange membrane, the proton conductivity is improved and methanol permeability is reduced, and the problems of low conductivity and high methanol permeability in the prior art are solved, thereby achieving efficient DMFC performance.

CN119627161APending Publication Date: 2025-03-14HUBEI ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411019958.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing DMFC proton exchange membrane has low proton conductivity and high methanol permeability, making it difficult to simultaneously improve the conductivity and reduce methanol permeability.

Method used

Using a SPBI-based composite proton exchange membrane containing sulfonated octphenyl SPOSS, the high ion exchange capacity of SPOSS and the sulfonate group are used to conduct acid-base cross-linking with the imidazole group of SPBI, which improves the proton conductivity and prevents methanol penetration through the incorporation of SPOSS.

Benefits of technology

A composite proton exchange membrane with excellent comprehensive performance with low methanol permeability and high conductivity is achieved, which improves the battery performance and mechanical stability of DMFC.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627161A_ABST
    Figure CN119627161A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of direct methanol fuel cells, and particularly relates to a preparation method and application of an SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS, and the preparation method comprises the following steps: (1) preparing SPBI with high substitution degree through ring-opening reaction of cyclic lactone; (2) preparing sulfonated octaphenyl POSS (SPOSS) by adopting a chlorosulfonic acid sulfonation method; (3) dissolving the SPBI and the SPOSS obtained in the steps (1) and (2) in a good solvent, and casting to form a film; and (4) soaking the membrane obtained in the step (3) in an acid solution for ion self-crosslinking, washing with deionized water, and drying to obtain the composite proton exchange membrane. The SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS prepared by the invention has the advantages of high proton conductivity and power density, low methanol permeability, good mechanical property and thermal stability and the like, and is a proton exchange membrane material with excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of direct methanol fuel cells, and in particular to an SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS, and a preparation method and application thereof. Background Art

[0002] Direct methanol fuel cell (DMFC) is a clean and efficient energy conversion device that can directly convert the chemical energy stored in liquid methanol fuel into electrical energy and produce water and carbon dioxide, which can be reduced to methanol to achieve carbon cycle. DMFC is small in size and light in weight; it has a low operating temperature (about 80°C); it has a high energy density and can be used as an effective power source for many portable devices. Methanol is widely available, low in cost, green and sustainable, and the transportation and storage of liquid methanol is more convenient and safer than hydrogen, so DMFC is gradually receiving more and more attention.

[0003] As the core component of DMFC, proton exchange membrane (PEM) has a crucial impact on the performance of the battery. PEM needs to have high proton conductivity and single cell performance, low methanol permeation, excellent mechanical properties and thermal stability. Polybenzimidazole (PBI) and its derivatives are semi-crystalline polymers with high Young's modulus, high thermal decomposition temperature, excellent oxidation stability and chemical stability. However, they do not have proton conductivity by themselves. By introducing proton conductive groups such as sulfonic acid groups (-SO3H) into PBI, the resulting SPBI membrane can be endowed with ion conductive properties. However, the conductivity of pure SPBI membranes is relatively low because most of the sulfonic acid groups are neutralized by basic imidazole groups and can no longer contribute to proton conductivity.

[0004] Methanol permeability occurs via a diffusion mechanism, where methanol molecules diffuse through membrane pores and hydrophilic channels. Similar to water absorption and proton conductivity, methanol permeation increases with the increase of cationic groups in the membrane and the increase of temperature. How to solve the problem of increasing proton conductivity while reducing methanol permeation is a challenge in the current DMFC field. Octaphenyl POSS{(C6H5SiO 1.5 )8} is a hybrid inorganic-organic nanoparticle with an octahedral structure. Its denser inorganic core can inhibit the chain motion of polymer molecules and give the hybrid material good heat resistance. The corresponding phenyl organic substitution gives the hybrid material good reactivity. These special octahedral structures containing organic phenyl groups on the outer surface can be modified in multiple directions and made compatible with many polymer matrices, but they are rarely used in the field of DMFC proton exchange membranes in the prior art.

[0005] Therefore, it is necessary to develop a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS with low methanol permeability and high conductivity, as well as a preparation method and application thereof. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the above-mentioned background technology and provide a low methanol permeability, high conductivity SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS and a preparation method and application thereof. SPOSS is incorporated into the SPBI substrate, and the SPBI substrate provides excellent mechanical properties and thermal stability. The addition of SPOSS solves the problems of low proton conductivity and single cell performance of pure SPBI membrane and high methanol permeability, and obtains a composite membrane with excellent comprehensive performance.

[0007] The technical solution of the present invention is: a method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS, characterized in that it comprises the following steps:

[0008] (1) preparing side chain sulfonated polybenzimidazole SPBI by reacting polybenzimidazole PBI with sultone through a lactone ring-opening reaction;

[0009] (2) preparing sulfonated octaphenyl POSS by sulfonating octaphenyl POSS with chlorosulfonic acid;

[0010] (3) dissolving the side chain sulfonated polybenzimidazole SPBI obtained in step (1) and the sulfonated octaphenyl SPOSS obtained in step (2) in a solvent, and casting to prepare an SPBI / SPOSS composite membrane;

[0011] (4) The SPBI / SPOSS composite membrane obtained in step (3) is immersed in an acidic solution for self-crosslinking, and then washed with deionized water and dried to obtain the composite proton exchange membrane.

[0012] Preferably, in step (1), the synthesis route of the side chain sulfonated polybenzimidazole SPBI is as follows:

[0013]

[0014] Wherein: n=1 or 2, m is 60 to 400;

[0015] The SPBI synthesis steps specifically include: dissolving polybenzimidazole PBI in a good solvent A, adding a slightly excess dehydrogenation reagent under N2 protection, and reacting at 40-60°C for 3-4 hours; then adding a certain amount of sultone to the reaction system after dehydrogenation, wherein the sultone is 1,3-propanesultone or 1,4-butanesultone, and continuing the reaction at the original temperature for 12-15 hours; after the reaction is completed, the SPBI powder is obtained through purification.

[0016] Preferably, the good solvent A is dimethyl sulfoxide (DMSO) or dimethylformamide (DMF), the dehydrogenation agent is one of sodium hydride, lithium hydride, sodium hydroxide or potassium hydroxide, and the molar ratio of the polymerization unit, dehydrogenation agent and sultone contained in the PBI is 1:(2-10):(2-10). Furthermore, the molar ratio of the polymerization unit, dehydrogenation agent and sultone contained in the PBI is 1:6:7.46. The polymerization unit contained in PBI is:

[0017]

[0018] By controlling the feeding of sultone, SPBI with different sulfonation degrees is prepared, and the sulfonation degree ranges from 100% to 200%. The sulfonation degree is preferably 150% to 200%, and more preferably 180% to 200%. SPBI with such substitution degree has better ionic conductivity when used in the present invention.

[0019] Furthermore, the purification treatment in step (1) includes: slowly dripping the reaction solution into a precipitating agent to precipitate the product, washing, centrifuging, and vacuum drying to obtain SPBI powder. The precipitating agent is acetone, ethanol, or ether, and the washing is first washed once with a 0.5-2M sodium carbonate or potassium carbonate solution to eliminate crosslinking that occurs during the reaction; and finally washed 3-5 times with distilled water and ethanol respectively to remove impurities.

[0020] Preferably, in step (2), the synthesis route of sulfonated octaphenyl SPOSS is as follows:

[0021]

[0022] The synthesis step of sulfonated octaphenyl SPOSS specifically includes: dissolving octaphenyl POSS in chlorosulfonic acid, wherein the molar ratio of the octaphenyl POSS to the chlorosulfonic acid is 1:(50-100), stirring the mixture at room temperature for 24-48 hours at a speed of 300-600 r / min; after the reaction is completed, the mixture is purified to obtain SPOSS powder. Furthermore, the molar ratio of the octaphenyl POSS to the chlorosulfonic acid is 1:63.7.

[0023] Furthermore, the purification treatment in step (2) includes: slowly dropping the reaction solution into crushed ice to precipitate the product, washing, centrifuging and drying to obtain SPOSS powder. The washing step includes washing with ice water and tetrahydrofuran for multiple times.

[0024] Preferably, in step (3), the SPBI / SPOSS composite membrane preparation step specifically includes: dissolving SPBI and SPOSS in a good solvent B respectively, mixing the two solutions after forming a uniform solution, continuing to heat and stir at 100-150°C for 6-12h to make it a uniform casting liquid, then pouring the casting liquid onto a glass plate, and drying at 60-100°C for 48-72h to remove the solvent to obtain an SPBI / SPOSS composite membrane.

[0025] Further, the good solvent B is dimethyl sulfoxide DMSO or dimethylformamide DMF, and the mass ratio of SPOSS: (SPBI + SPOSS) = (1-25): 100. That is, the mass percentage of SPOSS in the SPBI / SPOSS composite film is 1%-25%. Further, the mass ratio of SPOSS: (SPBI + SPOSS) = (1-10): 100, that is, the mass percentage of SPOSS in the SPBI / SPOSS composite film is 1%-10%.

[0026] Furthermore, the thickness of the SPBI / SPOSS composite film is 20±1 μm, which means that the thickness of the SPBI / SPOSS composite film is 19-21 μm.

[0027] Preferably, in step (4), the acidic solution has a concentration of 0.5M to 2M and the immersion time is 12 to 48 hours. Under acidic conditions, the sulfonic acid groups on SPBI and SPOSS undergo acid-base crosslinking with the imidazole groups on SPBI to form a crosslinked structure.

[0028] The present invention also provides an SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS, which is prepared by any of the above methods for preparing the SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS.

[0029] The present invention also provides an application of an SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS, which is applied to a proton exchange membrane of a direct methanol fuel cell.

[0030] The present invention uses sulfonated polybenzimidazole (SPBI) as a substrate and dopes sulfonated octaphenyl POSS (i.e., SPOSS) to prepare a SPBI-based composite proton exchange membrane containing SPOSS. POSS is considered to be the smallest silica particle. First, its hollow cage structure can absorb and retain water, thereby increasing the conductivity; second, SPOSS has a relatively high IEC value, which can increase the proton density and thus the conductivity; in addition, the sulfonic acid group on SPOSS can undergo acid-base crosslinking with the imidazole group on SPBI, thereby releasing part of the sulfonic acid group on SPBI, further increasing the proton conductivity; finally, the incorporation of SPOSS can serve as a barrier to prevent methanol penetration, while changing the tortuous diffusion pathway to reduce methanol penetration. The doping of SPOSS solves the problem of increasing proton conductivity while reducing methanol penetration.

[0031] The beneficial effects of the present invention are:

[0032] 1. Polybenzimidazole (PBI) and its derivatives are semi-crystalline polymers with high Young's modulus, excellent mechanical properties and thermal stability.

[0033] 2. SPOSS contains silicon dioxide, and it is a body-shaped structure that can absorb and retain water, thereby increasing proton conductivity;

[0034] 3. SPOSS has a relatively high ion exchange capacity (IEC), IEC up to 3mmol*g -1 , which can increase the proton density and improve the conductivity.

[0035] 4. The sulfonic acid groups on SPOSS can undergo acid-base crosslinking with the imidazole groups on SPBI, thereby releasing some of the sulfonic acid groups on SPBI and further improving proton conductivity;

[0036] 5. The incorporation of SPOSS can act as a barrier to prevent methanol penetration and increase the tortuous diffusion pathway, thereby reducing methanol penetration. An SPBI-based composite proton exchange membrane containing sulfonated octaphenyl POSS with excellent comprehensive performance is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The proton conductivity of the SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS prepared in the embodiment of the present invention.

[0038] Figure 2 This is a power density curve of the SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS prepared in an embodiment of the present invention using 2M methanol as fuel.

[0039] Figure 3This is a graph showing the methanol permeation limiting current density of the SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS prepared in an embodiment of the present invention using 2M methanol as fuel.

[0040] Figure 4 This is a stress-strain curve of the SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS prepared in an embodiment of the present invention in a wet state. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The drugs used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods in the art unless otherwise specified.

[0042] Example 1

[0043] This embodiment provides a method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS, the steps of which are as follows:

[0044] (1) Synthesis of SPBI: 5 g (containing 12.5 mmol of polymerized units) of polybenzimidazole was dissolved in 250 mL of DMSO. Under the protection of N2, 3 g (75 mmol) of sodium hydride was added as a base catalyst. The mixture was stirred and heated to 50°C for 4 h. Then, 11.4 g (93.3 mmol) of 1,3-propanesulfonate was added to the dehydrogenated reaction system to form solution 1. The mixture was stirred at 50°C for 13 h. After the reaction, solution 1 was slowly poured into a large amount of acetone to obtain a yellow precipitate. After centrifugation, the precipitate was washed once with a 1 M sodium carbonate solution, and then washed three times with deionized water and ethanol respectively. The precipitate was dried under vacuum at 50°C for 24 h to obtain 5.5 g of yellow powder. The degree of sulfonation was 198%, so it was named SPBI. 198% , yield 64.1%;

[0045] (2) Synthesis of SPOSS: 6.98 g (6.75 mmol) of octaphenyl POSS was dissolved in 50 g (0.43 mol) of chlorosulfonic acid to form solution 2, and the mixture was stirred at room temperature for 48 h at a speed of 600 r / min. After the reaction, solution 2 was slowly dripped into a large amount of excess crushed ice to precipitate a white precipitate, which was then washed three times with 150 mL of ice water and tetrahydrofuran, respectively, centrifuged and dried in an oven at 65° C. for 48 h to obtain 3.43 g of a brown solid with a yield of 31%.

[0046] (3) Casting method: 0.2475g SPBI was dissolved in 15mL DMSO to form solution 3, 0.0025g SPOSS was dissolved in 15mL DMSO to form solution 4, solutions 3 and 4 were heated and stirred at 120°C for 6h, and after a uniform solution was formed, solutions 3 and 4 were mixed to form solution 5, and the mixture was heated and stirred at 120°C for 6h to form a uniform casting solution, and impurities were removed by filtration, and then solution 5 was poured onto a 10×10cm glass plate, and the glass plate was placed on a hot plate at 60-100°C and heated for 48h to remove the solvent DMSO, and the film was carefully removed after it was detached from the glass plate. The mass fraction of SPOSS in the composite film was 1%, which was recorded as SPBI-1% SPOSS. The film thickness was 20μm.

[0047] (4) The membrane obtained by S3 was immersed in a 1M H2SO4 solution at room temperature for 24 h for ion cross-linking, and then washed with deionized water until neutral and dried to obtain an SPBI-based composite proton exchange membrane containing sulfonated octaphenyl POSS.

[0048] Example 2

[0049] This embodiment provides a method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS.

[0050] (1) Synthesis of SPBI: 5 g (containing 12.5 mmol of polymerized units) of polybenzimidazole was dissolved in 250 mL of DMSO. Under the protection of N2, 3 g (75 mmol) of sodium hydride was added as a base catalyst. The mixture was stirred and heated to 50°C for 4 h. Then, 11.4 g (93.3 mmol) of 1,3-propanesulfonate was added to the dehydrogenated reaction system to form solution 1. The mixture was stirred at 50°C for 12 h. After the reaction, solution 1 was slowly poured into a large amount of acetone to obtain a yellow precipitate. After centrifugation, the precipitate was washed once with a 1 M sodium carbonate solution, and then washed three times with deionized water and ethanol respectively. The precipitate was dried under vacuum at 50°C for 24 h to obtain 5.6 g of yellow powder. The degree of sulfonation was 198%, so it was named SPBI. 198% , yield 65.3%.

[0051] (2) Synthesis of SPOSS: Prepare according to step (2) of Example 1.

[0052] (3) Casting method: 0.2425 g SPBI was dissolved in 15 mL DMSO to form solution 3, 0.0075 g SPOSS was dissolved in 15 mL DMSO to form solution 4, solutions 3 and 4 were heated and stirred at 120 ° C for 6 h, and after a uniform solution was formed, solutions 3 and 4 were mixed to form solution 5, and the mixture was heated and stirred at 120 ° C for 6 h to make it a uniform casting solution, and impurities were removed by filtration. Then solution 5 was poured onto a 10×10 cm glass plate, and the glass plate was placed on a hot plate at 60-100 ° C for 48 h to remove the solvent DMSO, and the film was carefully removed after it was detached from the glass plate. The mass fraction of SPOSS in the composite film was 3%, recorded as SPBI-3% SPOSS. The film thickness was 19 μm.

[0053] (4) The membrane obtained by S3 was immersed in a 1M H2SO4 solution at room temperature for 24 h for ion cross-linking, and then washed with deionized water until neutral and dried to obtain an SPBI-based composite proton exchange membrane containing sulfonated octaphenyl POSS.

[0054] Example 3

[0055] This embodiment provides a method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS, which is different from the method in embodiment 2 only in that the amount of SPBI and SPOSS in step (3) is adjusted so that the mass fraction of SPOSS in the composite membrane is 5%, that is, the mass sum of (SPBI+SPOSS) remains unchanged at 0.25g, and the mass ratio of SPOSS: (SPBI+SPOSS) = 5%. The membrane thickness is 21 μm.

[0056] Finally, a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl POSS was obtained, and the mass fraction of SPOSS in the composite membrane was 5%, which was recorded as SPBI-5% SPOSS.

[0057] Example 4

[0058] This embodiment provides a method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS, which is different from that in embodiment 2 only in that the amount of SPBI and SPOSS in step (3) is adjusted so that the mass fraction of SPOSS in the composite membrane is 7%, that is, the mass sum of (SPBI+SPOSS) remains unchanged at 0.25g, and the mass ratio of SPOSS: (SPBI+SPOSS) = 7%. The membrane thickness is 19 μm.

[0059] Finally, a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl POSS was obtained, and the mass fraction of SPOSS in the composite membrane was 7%, which was recorded as SPBI-7% SPOSS.

[0060] Example 5

[0061] This embodiment provides a method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS, which is different from the method in embodiment 2 only in that the amount of SPBI and SPOSS in step (3) is adjusted so that the mass fraction of SPOSS in the composite membrane is 10%, that is, the mass sum of (SPBI+SPOSS) remains unchanged at 0.25 g, and the mass ratio of SPOSS: (SPBI+SPOSS) = 10%. The membrane thickness is 20 μm.

[0062] Finally, a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl POSS was obtained, in which the mass fraction of SPOSS was 10%, and was recorded as SPBI-10% SPOSS.

[0063] Comparative Example

[0064] This comparative example provides a method for preparing an SPBI-based ion exchange membrane, which differs from Example 2 only in that SPOSS is not used in step S3. Finally, a pure SPBI membrane is obtained, which is denoted as SPBI 198% The film thickness was 19 μm.

[0065] Performance Testing

[0066] The proton conductivity of the composite proton exchange membrane prepared in Examples 1-5 and Comparative Examples is as follows: Figure 1 shown.

[0067] Test method: The membrane was cut into 1×3 cm rectangles and the membrane resistance (R) was tested at different temperatures (20-80°C) using an electrochemical workstation (Autolab PGSTAT 302N, Switzerland). The test frequency range was 1-10 6 Hz, AC signal amplitude is 50mV. The calculation formula of ionic conductivity σ (S / cm) is as follows: σ = L / R x A

[0068] Where L (cm) is the distance between the two electrodes. In this work, L = 2.16 cm, A (cm 2 ) is the effective cross-sectional area of ​​the membrane to be measured between the two electrodes, and R (Ω) is the resistance of the membrane.

[0069] from Figure 1 It can be seen that with the increase of SPOSS content, the proton conductivity of the composite membrane gradually increases, among which the proton conductivity of the SPBI-7% SPOSS composite membrane is the highest, which is 117.5 mS cm -1 , is pure membrane SPBI 198% When the mass fraction of SPOSS reaches 10%, its conductivity decreases. This is because with the increase of SPOSS, the size of the aggregates in the composite membrane increases, and the agglomeration destroys the proton transport channel, resulting in a decrease in conductivity.

[0070] The power density curve of the composite proton exchange membrane prepared in Examples 1-5 and Comparative Examples using 2M methanol as fuel is shown in FIG. Figure 2 shown.

[0071] Test method: Before the test, the membrane to be tested was made into a membrane electrode assembly (MEAs) (2.0 cm × 2.0 cm) by hot pressing, and hot pressed at 2 MPa pressure and 130 ° C for 3 minutes. The catalyst used in the anode was Pt-Ru, with a loading of 4.0 mg cm -2 , the cathode is Pt, and the loading amount is 2.0 mg cm -2 The catalysts used were purchased from commercial channels. The cell performance of the prepared membrane was evaluated at 80 °C. The prepared membrane electrode assembly was installed in a single cell, and methanol fuel (1MH2SO4+2M MeOH) was delivered to the anode at a flow rate of 1 mL min -1 , oxygen is delivered to the cathode at a flow rate of 100 mL min -1 The current density (I) and potential (V) curves of the single cell were recorded by an electrochemical workstation (Autolab PGSTAT 302N, Switzerland).

[0072] from Figure 2 It can be seen that the peak power density of all membranes shows the same trend as the proton conductivity, that is, it first increases and then decreases with the increase of SPOSS content. The maximum peak power density of SPBI-7% SPOSS is 130.5 mW cm -2 , is pure membrane SPBI 198% 1.25 times of.

[0073] The methanol permeation limiting current density curve of the composite proton exchange membrane prepared in Examples 1-5 and Comparative Examples with 2M methanol as fuel is as follows: Figure 3 shown.

[0074] Test method: The prepared MEAs were installed in a single cell. The test temperature was 80°C, and the anode was fed with 1M H2SO4+2MMeOH fuel at a flow rate of 1mL min -1 , the cathode is supplied with nitrogen at a flow rate of 100 mL min -1 Methanol permeation was tested in situ by applying a positive potential to a single direct methanol fuel cell to oxidize the permeated methanol in the cathode. The methanol permeation current density of all membranes was recorded by an electrochemical workstation (Autolab PGSTAT 302N, Switzerland).

[0075] Figure 3 The results show that the methanol permeation limiting current density of all composite membranes is lower than that of pure membranes. The methanol permeation limiting current density of SPBI-7% SPOSS is 142 mA cm -2 , reduced to pure membrane SPBI198% 73%, indicating that the incorporation of SPOSS can act as a barrier to prevent methanol penetration, increase the diffusion pathway of methanol, and thus reduce methanol penetration.

[0076] The stress-strain curves of the composite proton exchange membranes prepared in Examples 1-5 and Comparative Examples in a wet state are as follows: Figure 4 shown.

[0077] Test method: The film was cut into rectangles of 1×4 cm, and its mechanical properties in wet state were tested using a tensile tester (AG-IC 5KN, Shimadzu Corporation, Japan) at a tensile rate of 50 mm min -1 .

[0078] from Figure 4 It can be seen that all membranes have excellent mechanical properties, among which the tensile strength of the composite membranes with SPOSS mass fractions of 1%, 3%, 5%, and 7% are all greater than 31.7MPa and the strain is greater than 80.4%, which are fully suitable for PEM in DMFC.

Claims

1. A method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS, characterized in that: The following steps are involved: (1) preparing side chain sulfonated polybenzimidazole SPBI by reacting polybenzimidazole PBI with sultone through a lactone ring-opening reaction; (2) preparing sulfonated octaphenyl POSS by sulfonating octaphenyl POSS with chlorosulfonic acid; (3) dissolving the side chain sulfonated polybenzimidazole SPBI obtained in step (1) and the sulfonated octaphenyl SPOSS obtained in step (2) in a solvent, and casting to prepare an SPBI / SPOSS composite membrane; (4) The SPBI / SPOSS composite membrane obtained in step (3) is immersed in an acidic solution for self-crosslinking, and then washed with deionized water and dried to obtain the composite proton exchange membrane.

2. The method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS as claimed in claim 1, characterized in that: In step (1), the synthesis route of side chain sulfonated polybenzimidazole SPBI is as follows: Wherein: n=1 or 2, m is 60 to 400; The SPBI synthesis steps specifically include: dissolving polybenzimidazole PBI in a good solvent A, adding a slightly excess dehydrogenation reagent under N2 protection, and reacting at 40-60°C for 3-4 hours; then adding a certain amount of sultone to the reaction system after dehydrogenation, wherein the sultone is 1,3-propanesultone or 1,4-butanesultone, and continuing the reaction at the original temperature for 12-15 hours; after the reaction is completed, the SPBI powder is obtained through purification.

3. The method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS as claimed in claim 2, characterized in that: The good solvent A is dimethyl sulfoxide (DMSO) or dimethylformamide (DMF), the dehydrogenation agent is one of sodium hydride, lithium hydride, sodium hydroxide or potassium hydroxide, and the molar ratio of the polymerization unit, the dehydrogenation agent and the sultone contained in the PBI is 1:(2-10):(2-10).

4. The method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS as claimed in claim 1, characterized in that: In step (2), the synthetic route of sulfonated octaphenyl SPOSS is as follows: The synthesis steps of sulfonated octaphenyl SPOSS specifically include: dissolving octaphenyl POSS in chlorosulfonic acid, wherein the molar ratio of the octaphenyl POSS to the chlorosulfonic acid is 1:(50-100), stirring and reacting at room temperature for 24-48 hours at a rotation speed of 300-600r / min; after the reaction is completed, the SPOSS powder is purified.

5. The method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS as claimed in claim 1, characterized in that: In step (3), the SPBI / SPOSS composite membrane preparation steps specifically include: dissolving SPBI and SPOSS in a good solvent B respectively, mixing the two solutions after forming a uniform solution, continuing to heat and stir at 100-150°C for 6-12 hours to make it a uniform casting liquid, then pouring the casting liquid onto a glass plate, and drying at 60-100°C for 48-72 hours to remove the solvent to obtain an SPBI / SPOSS composite membrane.

6. The method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS as claimed in claim 5, characterized in that: The good solvent B is dimethyl sulfoxide (DMSO) or dimethylformamide (DMF), and the mass ratio of SPOSS:(SPBI+SPOSS)=(1-25):

100.

7. The method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS as claimed in claim 5, characterized in that: The thickness of the SPBI / SPOSS composite film is 20±1 μm.

8. The method for preparing a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS according to claim 1, characterized in that: In step (4), the acidic solution is sulfuric acid or hydrochloric acid with a concentration of 0.5M to 2M, and the soaking time is 12 to 48 hours.

9. A SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS, characterized in that: The invention is prepared by the preparation method of any one of claims 1 to 8 for a SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS.

10. An application of the SPBI-based composite proton exchange membrane containing sulfonated octaphenyl SPOSS as claimed in claim 9, characterized in that: Applied to proton exchange membrane of direct methanol fuel cell.